Protecting the Patient’s Data in the 21st Century Healthcare Industry: Is the African Continent Ready for the Digital Space? - Maduekwe , Nkiruka Chidia (Journal of Sustainable Development Law and Policy, 2025)
To ensure proper healthcare services and automation, including minimising medical errors and providing faster and more efficient healthcare, the medical field is experiencing innovative technological trends. They include automated patient records, hospital management system software, telemedicine, and the use of artificial intelligence devices. These innovations exist in more than just the global north, as they are slowly finding residence in African countries. Focusing on automated patient record, the article examines existing data protection legal frameworks in Africa to ascertain whether they provide effective remedy mechanisms patients can access should a breach occur. Taking cognisance of the current African Continental Free Trade Area Agreement (AfCFTA) aimed at creating a single market for goods and services; it is evident that healthcare services might have a continental approach. Thus, the article adopts a continental, regional, and national perspective. Using doctrinal method, the article compares the African Union Data Protection Convention with the European Union General Data Protection Regulation to draw lessons from the European Union Experience. The article finds that strengthened national mechanisms might provide the requisite remedy mechanisms patients can access to ensure enforcement of their rights to data protection.